2023
DOI: 10.1038/s41467-023-43418-5
|View full text |Cite
|
Sign up to set email alerts
|

SLC35D3 promotes white adipose tissue browning to ameliorate obesity by NOTCH signaling

Hongrui Wang,
Liang Yu,
Jin’e Wang
et al.

Abstract: White adipose tissue browning can promote lipid burning to increase energy expenditure and improve adiposity. Here, we show that Slc35d3 expression is significantly lower in adipose tissues of obese mice. While adipocyte-specific Slc35d3 knockin is protected against diet-induced obesity, adipocyte-specific Slc35d3 knockout inhibits white adipose tissue browning and causes decreased energy expenditure and impaired insulin sensitivity in mice. Mechanistically, we confirm that SLC35D3 interacts with the NOTCH1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Previous studies have demonstrated that the activation of Notch1 signaling promotes adipocyte proliferation [ 19 ], while the modulation of the Notch1 signal in adipose tissue macrophages is crucial for regulating inflammation and metabolism [ 20 ]. Moreover, inhibiting Notch1 expression has been shown to significantly enhance brown fat thermogenesis, promote white fat browning, and ameliorate obesity [ 21 , 22 , 23 ]. Although EGCG can improve inflammation by inhibiting Notch1 and has significant effects on obesity [ 11 , 24 ], it is still uncertain whether EGCG in adipose tissue can have the same metabolic-promoting and obesity-improving effects by targeting Notch1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the activation of Notch1 signaling promotes adipocyte proliferation [ 19 ], while the modulation of the Notch1 signal in adipose tissue macrophages is crucial for regulating inflammation and metabolism [ 20 ]. Moreover, inhibiting Notch1 expression has been shown to significantly enhance brown fat thermogenesis, promote white fat browning, and ameliorate obesity [ 21 , 22 , 23 ]. Although EGCG can improve inflammation by inhibiting Notch1 and has significant effects on obesity [ 11 , 24 ], it is still uncertain whether EGCG in adipose tissue can have the same metabolic-promoting and obesity-improving effects by targeting Notch1.…”
Section: Introductionmentioning
confidence: 99%